Two‐Photon Excitation of a Plasmonic Nanoswitch Monitored by Single‐Molecule Fluorescence Microscopy. Issue 21 (8th April 2016) - Impellizzeri, Stefania; Simoncelli, Sabrina; Hodgson, Gregory K.; Lanterna, Anabel E.; McTiernan, Christopher D.; Raymo, Françisco M.; Aramendia, Pedro F.; Scaiano, Juan. C.
Abstract: Visible‐light excitation of the surface plasmon band of silver nanoplates can effectively localize and concentrate the incident electromagnetic field enhancing the photochemical performance of organic molecules. Herein, the first single‐molecule study of the plasmon‐assisted isomerization of a photochrome‐fluorophore dyad, designed to switch between a nonfluorescent and a fluorescent state in response to the photochromic transformation, is reported. The photochemistry of the switchable assembly, consisting of a photochromic benzooxazine chemically conjugated to a coumarin moiety, is examined in real time with total internal reflection fluorescence microscopy in the presence of silver nanoplates excited with a 633 nm laser. The metallic nanostructures significantly enhance the visible light‐induced performance of the photoconversion, which normally requires ultraviolet excitation. The resulting ring‐open isomer is strongly fluorescent and can also be excited at 633 nm. These stochastic emission events are used to monitor photochromic activation and show quadratic dependence on incident power. The utilization of a single laser wavelength for both photochromic activation and excitation effectively mimics a pseudo two‐colours system. Abstract : The first single‐molecule study of the plasmon‐assisted isomerization of a photochrome‐fluorophore dyad, designed to switch between a nonfluorescent and a fluorescent state in response to the photochromic transformation, is reported. The photochemistry of the switchable assembly is examined in real time with total internal reflection fluorescence microscopy in the presence of silver nanoplates excited with a 633 nm laser (see figure)